(untitled) (Ameghiniana, 2003)
The present paper deals with sonie fragments of two differents specimens wich belong to a new Cardiatheriinae: Neoanchimys Pisanoi gen. et sp. nov. They have been found in the Upper Pliocene ("Hermosense") in silstones from the. Monte Hermosa cliffs, Buenris Aires Province, Argentina. In the first part we analyze and critically synthesize L. Kraglievich’s interpretation of the phylogeny and morphological variations of the cheek-tc eth of these primitive South American "carpinchos’’. In order to get a nomenclatorial adjustment suited for the descriptions of the lower cheek-teeth, a system composed by signs of the terms proposed by.Rusconi·for the premolar. and .by Kraglievich for. all the molarifoims, is integrated. After the description, in the second part, the chararacters of this new taxon are analyzed. It is considered as direct descendant of the Eucardiodon-Anchimys group, We consider this new genus as belonging to a distinct line from the one that Kraglievich ended with Cardiatherium. On the basis of the morphology of the molariforms we consider the Eucardiodon-Anchimys group as ancestor of the Hydrochoerinae as Plexochoerus or Cardiatherium could be, following Kraglievich’s interpretation. The examination of the material of the Cardiatheriinae from the Argentinian Pliocene suggests that the phylogehetic hiStory of these rodents must have been more complicated and not as ortogenetic as Kraglievich pretended.